Influence Analysis of Heating Time Towards Degradation of Anti Oxidant Activity on Water Spinach Leaves (Ipomoea Aquatica Forsk) - Arsyad, Akhmad Baihaqi; Nirwana, Ratih Rizqi; Firmansyah, R. Arizal (Journal Of Natural Sciences And Mathematics Research, 2016)
The purpose of this research is to analyze the impact of water spinach leaves heating (Ipomoea aquatica Forsk) at 100oC by different time duration on its antioxidant activity. The method was experimental method involved several steps, such as sample preparation, extraction process, and evaluation of antioxidant activity with UV-Visible Spectrophotometer. The result of this research shown that IC50 value from K1, K2, K3 to K4 were 25.25 Î¼g/mL (very high), 96.75 Î¼g/mL (high), 181.47Î¼g/L (low, and 280Î¼g/mL (very low). The IC50 value of K1 to K2 decreased 71.49 Î¼g/L, The K2 to K3 decreased 84.72 Î¼g/L, K3 to K4 decreased 98.53 Î¼g/L. By this result, it was predicted that the antioxidant of water spinach will diminish, or even it will be lowered when it is steamed more than 15 minutes in 100 ï°C. Â©2016 JNSMR UIN Walisongo. All rights reserved.